Design and initial testing of an integrated switched reluctance starter/generator system for unmanned aerial vehicle - Erxin Zhao; Shoujun Song; Zhen Ma; Xueping Zhang; Le Ning; Yang Liu (CES Transactions on Electrical Machines and Systems, 2018)
According to specific performance requirements, an integrated switched reluctance starter/generator system, which can start the engine and supply electrical energy to the loads, is designed and manufactured for the unmanned aerial vehicle. Considering the required starting torque and speed range, the geometrical dimensions of the switched reluctance machine are calculated based on the output equation and further optimized with finite element analysis, and the flux-linkage, inductance and static torque characteristics are illustrated. To verify the performances of the designed system, detailed simulation with the model considering piston engine and experiment using the test bench are carried out.